Muscle Resting and TGF-β Inhibitor Treatment Prevent Fatty Infiltration Following Skeletal Muscle Injury - Pagano, Allan F; Arc-Chagnaud, Coralie; Brioche, Thomas; Chopard, Angèle; Py, Guillaume (Cellular physiology and biochemistry, 2019)
Skeletal muscle injuries are the most common type of injury occurring in sports, and investigating skeletal muscle regeneration as well as understanding the related processes is an important aspect of the sports medicine field. The process of regeneration appears to be complex and precisely orchestrated, involving fibro-adipogenic progenitors (FAPs) which are a muscle-resident stem cell population that appears to play a major role in abnormal development of fibrotic tissue or intermuscular adipose tissue (IMAT). Our present study aims to investigate whether muscle resting or endurance exercise following muscle injury may change the behavior of FAPs and subsequently impact the development of fatty infiltrations and fibrosis, two hallmarks of regeneration failure. We used the validated glycerol muscle injury model to mimic abnormal muscle regenerative conditions in mice. We challenged this specific regeneration model with hindlimb unloading or endurance exercise and, in a second set of experiments, we treated mice with decorin, a TGF-β inhibitor. In this study, we demonstrated that: i) muscle resting just after injury leads to inhibition of IMAT development, ii) TNF-α mediated FAP apoptosis might be perturbed in this specific glycerol model of muscle injury, leading to IMAT development, and iii) treatment with the TGF-β inhibitor decorin decreases IMAT development and might restores FAP apoptosis. In addition to the potential clinical relevance of decorin treatment in situations involving muscle plasticity and regeneration, this study also demonstrates that a period of muscle resting is necessary following muscle injury to achieve efficient muscle regeneration which is associated with a reduction in fatty infiltration. Unreasonably early resumption of exercise brings no gain to regeneration, further highlighting that this resting period is necessary.